Feeding juvenile marron (Cherax cainii Austin, 2002) exclusively on live mixed plankton improves growth, total haemocyte count and pigmentation - Gagnon, Monique; Tulsankar, Smita; Cole, Anthony; Fotedar, Ravi (Elsevier, 2021)
The present study aimed to compare the nutritional effects of a mixture of phytoplankton and zooplankton and a formulated pelleted feed on the growth, survival, moulting, immune and organosomatic indices of juvenile marron (Cherax cainii Austin, 2002) cultured for 90 days, under controlled laboratory conditions. The experiment was conducted with two quadruplicated dietary treatments, a pre-selected plankton density and formulated feed pellets (Control). Seventy two juvenile marron of an average weight of 3.73 ± 0.16 g and average total length of 2.57 ± 0.04 cm were collected from a local farm and reared in eight 300 L water capacity tanks. In treatment tanks, the phytoplankton and zooplankton density was maintained at the average of 2.81 ± 0.02 × 106 cells L−1 and 228 ± 5.15 individuals L-1 respectively. Marron in the control group were fed with formulated feed at 2% of marron’s body weight per day during the evening. Marron fed with mixed live plankton achieved a significantly higher growth rate, total haemocyte count and improvement in pigmentation of juvenile marron. Survival rate and organosomatic indices of juvenile marron were similar with the use of mixed plankton, and formulated feed. Therefore, from these results, it can be concluded that the live plankton can be a main source of nutrition for an early stage of juvenile marron, if the plankton density is maintained.